Photoluminescent layered lanthanide-organic framework based on a novel trifluorotriphosphonate organic linker - Vilela, Sergio M. F.
A series of fluorinated lanthanide-organic frameworks (LnOFs), formulated as [Ln(H(3)tftp)(H2O)] [where Ln(3+) = La3+ (1), (La0.95Eu0.05)(3+) (2), (La0.95Tb0.05)(3+) (3) and (La0.94Eu0.03Tb0.03)(3+) (4)], has been successfully prepared, under hydrothermal conditions, using the novel ((2,4,6-trifluorobenzene-1,3,5-triyl)tris (methylene)) triphosphonic acid (H(6)tftp) organic ligand and Ln(3+) cations as metallic centers. The three-step preparation of the tripodal H(6)tftp ligand is described. H(6)tftp and all intermediate molecules involved in the synthesis were fully characterized in the liquid and solid states. While the La3+-based LnOF material was isolated as single-crystals, with its crystal structure being fully described by single-crystal X-ray diffraction, phase identification of the Eu3+-and Tb3+-based materials was performed by powder X-ray diffraction. It is shown that the crystal structure of this isotypical series of materials is based on a neutral two-dimensional (2)(infinity)[Ln(H(3)tftp)(H2O)] coordination polymer placed in the ac plane of the unit cell, exhibiting a uninodal 4-connected square layered topology. It is shown that the most striking and supramolecular relevant interactions are classical O-H center dot center dot center dot O hydrogen bonds within the polymer, further contributing to the structural robustness of the layer. Prepared LnOFs were fully characterized in the solid state using elemental and thermogravimetric analysis, electron microscopy (SEM and EDS) and FT-IR spectroscopy. Compound 1 was further studied using solid-state NMR (P-31 HPDEC MAS and C-13H-1 CP MAS) and thermodiffractometry. Photoluminescent studies have been performed on the mixed-lanthanide materials 2 and 3.